Recording and producing audio for media - Alten, Stanley R. (Boston, MA : Course Technology, 2012)
"This book covers informational, perceptual, and aesthetic aspects of sound as they apply to each stage of the production process, from planning to postproduction. Aspiring musicians, sound engineers, and producers will also gain a fundamental understanding of the principles, technologies, and techniques of audio production and postproduction for media, including radio, television, film, music recording, interactive media, the Internet, and mobile media ... The relationship of computers to audio production is covered from a non-software-specific and non-computer-specific approach"--P. [4] of cover.
Pt. I. Principles -- Pt. II. Technology -- Pt. III. Production -- Pt. IV. Postproduction.
Includes bibliographical references (p. 661-668) and index.
Keywords: Sound -- Recording and reproducing; Sound -- Recording and reproducing -- Equipment and supplies; Sound -- Equipment and supplies